Adsorption of Thymol From Aqueous Solution Using Granulated Surfactant Initiated Modified Bentonite via Packed Column Method - Abdul Latif, M. H.; Mahmood, A. K.; Al - Abayaji, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The adsorption study of thymol, was carried out at (25Â±0.1) Â°C, using granulated surfactant modified Iraqi Na â€“ montmorillonite clay (initiated modified bentonite); in a down-flow packed column, the modified mineral was characterized by FT-IR spectroscopy.  A linear calibration graph for thymol was obtained, which obey Beer's law in the concentration range of 5-50 mg/L at 274 nm against reagent blank. Single-factor-at-a-time approach; showed that the equilibrium time required for complete adsorption was 45 minute with flow rate (4.0drop/ mint). The adsorption of thymol increased with rising pH of the adsorbate solution, increase of solute uptake when  the initial adsorbate concentration is increased. The adsorption is mostly physically in nature and fitted with Langmuir model. The result indicated that the pseudo-second-order kinetic models is fitted very well with the experimental data.